Transforming the Role of Pesantren in Food Security and Economy through Smart Farming LifeCycle - Wahyudi, M. Iman; Safiudin, Safiudin; Kurniawan, Ade Fakih; Syafrizal, Reza (Santri: Journal of Pesantren and Fiqh Sosial, 2024)
As an educational institution where communities live and interact, Pesantren must enhance its independence and management development, food security, and economic initiatives to support the sustainability of its academic processes. This paper outlines the best management practices related to food security and economic development for Pesantren. The methodology employed is a case study of Pesantren Assa'adah in Cikeusal Serang, utilizing a literature review to provide a foundational basis for the analysis. The findings indicate that waste management concepts have been effectively carried out by processing both organic and inorganic waste. Additionally, automatic watering systems with soil moisture sensors have been deployed near fish ponds, ensuring plants receive the essential water elements efficiently. This system is powered by solar energy, making it an environmentally friendly option. Furthermore, the student (santri) consume livestock and agricultural products, demonstrating that the pesantren has a sustainable resource source, reducing daily accommodation expenses. Smart farming can also serve as a basis for educational tourism. From an economic standpoint, these practices are being developed, and further research is anticipated to enhance Pesantren's financial prospects.